Design Of Steganography Application To Secure Messages Using Least Significant Bit (Lsb) Method Based On Android - Rahmat Purnomo (Technologia Journal, 2024)
The Internet, an interconnected network, has become one of the most widespread data communications medias in the world. With the development of various illegal information retrieval techniques, many people try to get information that does not belong to them. Various techniques to protect sensitive information from unauthorized persons are widely used to protect important information. Steganography is a technique for hiding message files from the public who know their existence. This technique is often used to avoid suspicion or people who want to know the contents of the message file. Steganography is the science and technique of writing hidden messages so that no one else knows about their existence. Therefore, the application of plain-text steganography is inserted into the Least Significant Bit (LSB) encrypted image carrier. This allows mobile users to send the author's message to the recipient securely..